Network pharmacology and molecular docking approach to elucidate the mechanisms of safflower, phellodendron, scutellaria baicalensis, coptis, and gardenia in hand–foot syndrome - Li, Pengxing; Chen, Lizhu; Liu, Jianhui (Frontiers in Medicine, 2024)
Background: Safflower, phellodendron, scutellaria baicalensis, coptis, and gardenia (SPSCG) are medicinal plants with a wide range of anti-inflammatory and antioxidant effects. However, the related mechanism of SPSCG against hand-foot syndrome (HFS) has yet to be revealed.To investigate the mechanisms of SPSCG in the treatment of HFS using the Network Pharmacology.Methods: Active ingredients and targets of SPSCG for HFS were screened by the Chinese Medicine Systems Pharmacology (TCMSP) and Swiss Target Prediction databases. Potential therapeutic targets were collected from the GeneCards and OMIM databases. Subsequently, protein-protein interactions (PPI), Gene Ontology (GO) annotations, and pathways from the Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed to investigate the potential mechanism of the SPSCG in HFS. Then, molecular docking and molecular dynamics simulations were performed to predict the binding interactions between the active compound and the core target.Finally, vitro experiments were used to verify the repair effect of key ingredients of SPSCG on cell damage caused by 5-Fluorouracil.Results: Quercetin, kaempferol, β-sitosterol, and stigmasterol were identified as the major active components of SPSCG. GO analysis showed a total of 1127 biological processes, 42 terms cellular components, and 57 molecular functions. KEGG analysis showed that the MAPK, TNF, and IL-17 signaling pathways were significantly enriched. The PPI analysis discovered that EGFR, CASP3, AKT1, CCND1, and CTNNB1 shared the highest centrality among all target genes. The experimental results confirmed that these SPSCG active ingredients could treat HFS by reducing inflammation reaction and promoting cell damage repair.SPSCG may alleviate HFS by exerting antioxidative effects and suppressing inflammatory responses.